Biomechanical, operative and biological aspects of the cervical margin relocation: a case report - Prado, Taiana Paola [UNESP]; Chun, Eliseo Pablo; Augusto, Marina Gullo; Bernardon, Paula; Grassi, Elisa Donaria Aboucauch [UNESP]; Saavedra, Guilherme De Siqueira Ferreira Anzaloni [UNESP]; Mathias-Santamaria, Ingrid Fernandes; Santamaria, Mauro Pedrine [UNESP]; De Andrade, Guilherme Schmitt (Editora Cubo, 2022)
The clinical success of tooth-colored indirect restorations has been confirmed in several studies. However, inlays and onlays restorations in Class II cavities with deep gingival margins can still be considered a clinical challenge. With the purpose of facilitating the execution of the operative procedures in intrasulcular margins and reducing the risk of restorative failures, the technique of cervical margin relocation has been explored as a noninvasive alternative to surgical crown lengthening. This work aims at discussing through a case report the biomechanical, operative and biological aspects in the treatment of teeth with deep gingival margins. Therefore, given the therapy applied in the clinical case presented, it is concluded that the cervical margin relocation with composite resin is advantageous since it eliminates the need for surgery, allowing the implementation of indirect restorations in fewer clinical sessions, not causing damage to periodontal tissues once it provided good finishing and polishing with the establishment of a correct emergence profile, allowing flawless maintenance of gingival health after one year.
Aspectos biomecânicos, operatórios e biológicos da recolocação da margem cervical com resina composta em cavidades classe II com margens profundas: um relato de caso
Keywords: Composite Resins; Dental Cavity Preparation; Dental marginal adaptation; Dental restoration failure; Inlays